2006
DOI: 10.1111/j.1540-8167.2006.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrow, Slow‐Conducting Isthmus Dependent Left Atrial Reentry Developing After Ablation for Atrial Fibrillation: ECG Characterization and Elimination by Focal RF Ablation

Abstract: Focally ablatable narrow isthmuses of slow conduction are critical for the majority of reentrant LAT occurring after ablation for AF. The role and presence of these isthmuses can be anticipated by observing significant isoelectric intervals between flutter waves on all 12-surface ECG leads. Their distinctive electrophysiological characteristics allow their identification and elimination by simple RF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 17 publications
4
95
0
7
Order By: Relevance
“…This is in keeping with other studies that identified isthmuses supporting macroreentrant circuits as low as 0.05 to 0.1 mV. 14,15 Breakout sources had a median voltage of 0.35 mV with a range from 0.14 to 0.48 mV. This overlap between nonconductive and active tissue critical to the The detailed activation and voltage maps that were created also raises the possibility of additional substrate-based treatment of potential circuits that have been identified.…”
Section: Discussionsupporting
confidence: 84%
“…This is in keeping with other studies that identified isthmuses supporting macroreentrant circuits as low as 0.05 to 0.1 mV. 14,15 Breakout sources had a median voltage of 0.35 mV with a range from 0.14 to 0.48 mV. This overlap between nonconductive and active tissue critical to the The detailed activation and voltage maps that were created also raises the possibility of additional substrate-based treatment of potential circuits that have been identified.…”
Section: Discussionsupporting
confidence: 84%
“…11,12 However, it does not indicate a focal mechanism, for example, automaticity or triggered activity.…”
Section: Differentiation Between Reentry and Focal Atmentioning
confidence: 99%
“…Nevertheless, performing linear lesions in dilated LA can be challenging due to the fact thatthey have to be longer than in not-dilated LA. The vast majority of arrhythmias that occur after CAAF are re-entrant (83%) [1][2][3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and use gaps in prior ablation lines. Elimination of the dominant arrhythmia may uncover, suppressed so far, ectopic foci.…”
Section: Wwwcardiologyjournalorgmentioning
confidence: 99%